2021
DOI: 10.32598/ijpcp.27.2.3030.1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Persian Version of Nomophobia Questionnaire

Abstract: Objective: To validate and normalize the Nomophobia Questionnaire (NMP-Q) for use in Iran. Method: This study was a correlation study. Participants in this study were 280 undergraduate students of Mashhad universities in 95-96 who were selected by multistage cluster sampling and responded into Persian version of Nomophobia Questionnaire (NMP-Q) and the Cell-Phone Over-Use Scale (COS). Forty participants answered the questionnaire again two weeks later to assess the validity of the test-retest. The data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Concurrent validity was equal to 0.51 and retest reliability was equal to 0.81. The results of confirmatory factor analysis also showed that all four factors of the main questionnaire were confirmed in the Persian version (Alizadeh et al, 2021). In the current study, the reliability of this questionnaire was obtained by Cronbach's alpha method for the subscale of loss of communication 0.68, inability to communicate 0.72, lack of access to information 0.73, and loss of comfort and convenience 0.71.…”
Section: Nomophobia Questionnairesupporting
confidence: 51%
See 1 more Smart Citation
“…Concurrent validity was equal to 0.51 and retest reliability was equal to 0.81. The results of confirmatory factor analysis also showed that all four factors of the main questionnaire were confirmed in the Persian version (Alizadeh et al, 2021). In the current study, the reliability of this questionnaire was obtained by Cronbach's alpha method for the subscale of loss of communication 0.68, inability to communicate 0.72, lack of access to information 0.73, and loss of comfort and convenience 0.71.…”
Section: Nomophobia Questionnairesupporting
confidence: 51%
“…This questionnaire was translated in Iran by Azadmanesh et al (2016). In the study of Alizadeh et al (2021), Cronbach's alpha of this questionnaire for subscales was reported between 0.74 and 0.88. Concurrent validity was equal to 0.51 and retest reliability was equal to 0.81.…”
Section: Nomophobia Questionnairementioning
confidence: 97%
“…This instrument is widely used to assess nomophobia worldwide. From this perspective, several studies have focused on the cross-cultural validation of NMP-Q: in Spain, [36][37][38] in Italy, 39,40 in Portugal, 41,42 in China, 43,44 in Germany, 45 in Greece, 46 Brazil, 47 Indonesia, 48 Iran, [49][50][51] Turkey. 52 Nomophobic symptoms are very prevalent in university students and often affect their academic performance.…”
Section: Introductionmentioning
confidence: 99%